MODIFIKASI DAN UJI KINERJA UNIT PENYOSOH PADA MESIN PENYOSOH BIJI HANJELI (MPBH-0219) - Wahyu K Sugandi; Ruminta Ruminta; Asep Yusuf; Theresia Romey (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
Hanjeli has a hard rind, so it takes a peeler and polisher to process it. One of the machines used is the Hanjeli Polishing Machine AGR-RM40 in the Faculty of Agriculture, Padjadjaran University. However, this machine has the disadvantage that most of the hanjeli seeds are crushed and are not polished. This is due to the polishing space which is quite narrow so that it puts great pressure on the hanjeli seeds during the polishing. Meanwhile, the existence of not polished hanjeli was caused by friction between the cylinders and hanjeli which is not maximum. Therefore, this machine needs to be modified to improve the results of a better polishing. The method used in this research was engineering with several stages, such as designing a polishing unit, analysis, and performance testing on hanjeli batu and hanjeli pulut. The modification of the Polishing Unit on Hanjeli Polishing Machine (MPBH-0219) has a cylinder length dimension of 167 mm and a diameter of 37.9 mm. Based on the performance test, this machine is good and worth using where actual capacity is obtained 35 kg / hour, 96 % engine efficiency, 58,46 % dumping yield, 0.50 performance, and 1.30 kW actual power requirements. Keywords: Hanjeli Polishing Machine, Modification, Performance Test.